Response Of Weed Seed Germination From Fruit Crops Planting Soil To Application Of Metsulfuron Methyl Herbicide And Rice Husk Biochar - Subhan Arridho (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2021)
This study aims to determine the effect of the pre-emergence application of the herbicide metsulfuron methyl on the soil mixed with rice husk biochar to the germination of weeds. This study used a factorial completely randomized design (CRD) with two levels of herbicide metsulfuron methyl (0 gr/ha and 300 gr/ha) and four levels of rice husk biochar (0%, 5%, 10%, and 15% of the total weight of the planting medium). The parameters observed were the number of weeds, wet weight of weeds, and dry weight of weeds. The results showed that the interaction of the herbicide metsulfuron methyl and rice husk biochar had no significant effect on weed germination. The single treatment of the herbicide metsulfuron methyl had a significant effect on the number of weeds, wet weight of weeds, and dry weight of weeds. Herbicides can reduce the number of germinated weeds, wet weight of weeds, and dry weight of weeds by 39.3%, 83.7%, and 84.7%, respectively. While the single treatment of rice husk biochar showed a significant effect on the number of weeds and dry weight of weeds. The 15% treatment of rice husk biochar was the best to reduce the number of germinated weeds, namely 76.6%. Rice husk charcoal has the potential to be an alternative to suppress weed seed germination in the soil without using herbicides.